Conceptual model of key predictors and consequences of customer satisfaction - Đurić, Nadja (Anali Ekonomskog fakulteta u Subotici, 2024)
Satisfied customers represent an important resource for a company. So far research has shown that customer satisfaction has an impact on the return on investment, the growth of the company’s market share, and shareholder value. The importance of research on customer satisfaction is seen in the fact that it most often leads to loyalty, which represents an important prerequisite to a company’s long-term profitability. In line with the significance of these two concepts in companies’ success, the topics of this research are the determinants of customer satisfaction and the relationship between satisfaction and loyalty. The goal of the research is the identification of key variables and the measurement of their respective impact on customer satisfaction. For the identification of key determinants, an adapted expectancy-disconfirmation model has been used. Satisfaction has been viewed as a function of customer expectations and percived product performance, and an additional component: the company’s image. This research was carried out on the territory of the Republic of Serbia through an online survey. The obtained conclusions can help companies in Serbia to better the quality of provided services, with the end goal being achieving an agreeable level of customer satisfaction and loyalty, and with it, higher profitability